DEMOCRATIC LEGITIMACY OF THE BRAZILIAN CONSTITUTIONAL JURISDICTION: A POWER OF MEMBERS NOT ELECTED BY THE PEOPLE - Gonçalves da Silva, Hailton (Revista Gênero e Interdisciplinaridade, 2024)
Constitutional jurisdiction from the 1988 Federal Constitution gave the Judiciary responsibility for controlling the constitutionality of norms, which has caused a certain conflict between constitutionalism and democracy, two sides of the same coin. Would it be possible and healthy for democracy for the Judiciary to declare unconstitutional a rule authored by the Legislative Branch, which is made up of members elected by the people? The answer is yes, despite existing criticisms, if there is dialogue and joint, cooperative work between the powers. This is only possible if the control carried out by the Judiciary can protect not only the integrity of the democratic procedure, but also other constitutional values. The research is carried out using bibliographic methodology. It concludes with the thought that the legitimacy of the members of the Judiciary, in addition to its provision in the Constitution, is constructed in practice as it is decided under the motivation of the constitutional text and laws originating from parliament and which represent the people.